TELEMEDICINE IN MULTIPLE SCLEROSIS MANAGEMENT - A LITERATURE REVIEW - Daria Marciniak,; Alicja Pełszyk,; Michał Cholewiński,; Natalia Kruszewska,; Natalia Ziółkowska,; Paweł Szajewski,; Agata Pluta,; Justyna Kącikowska,; Justyna Łapicka,; Natalia Rosół, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Telemedicine has gained importance in recent years as an essential element of care for patients with multiple sclerosis (MS), particularly during the COVID-19 pandemic, which has accelerated the development of digital tools and remote forms of support. Considering the chronic nature of MS and the need for regular symptom monitoring, telemedicine solutions are a valuable adjunct to traditional neurological care.Methods: This review aims to present the current possibilities for the use of telemedicine in MS, including remote neurological consultations, the use of wearable devices for functional monitoring, telerehabilitation, and online forms of psychological support. Publications from recent years available in the Pubmed database describing telemedicine tools, their capabilities, effectiveness, and limitations were analyzed.Results: Current evidence suggests that online consultations may constitute a viable alternative to in-person visits, improving access to care and satisfaction among patients. E-diaries do not increase medication adherence, suggesting that this tool has restricted efficacy in improving compliance. Wearable devices enable continuous monitoring of patients' functioning in everyday life. Telerehabilitation has been shown to be effective in improving physical functioning, balance, respiratory and cognitive functions. Some online psychological interventions have also been shown to be effective, particularly in reducing symptoms of depression and anxiety.Conclusions: Telemedicine provides valuable support for the care of patients with MS, offering benefits in disease monitoring, rehabilitation, and psychological support. However, further high-quality research is needed to optimize its use and identify areas for development.